2021
DOI: 10.1097/ccm.0000000000004969
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Dilational Tracheostomy for Coronavirus Disease 2019 Patients Requiring Mechanical Ventilation*

Abstract: OBJECTIVES: To assess the impact of percutaneous dilational tracheostomy in coronavirus disease 2019 patients requiring mechanical ventilation and the risk for healthcare providers. DESIGN: Prospective cohort study; patients were enrolled between March 11, and April 29, 2020. The date of final follow-up was July 30, 2020. We used a propensity score matching approach to compare outcomes. Study outcomes were formulated before data collection and analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Unfortunately, most guidelines were published at the beginning of the pandemic without data to sustain them. This year, several studies have attempted to investigate how ET affects COVID-19 outcomes [21][22][23]. However, whether ET improves COVID-19 outcomes is still controversial [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most guidelines were published at the beginning of the pandemic without data to sustain them. This year, several studies have attempted to investigate how ET affects COVID-19 outcomes [21][22][23]. However, whether ET improves COVID-19 outcomes is still controversial [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that patients with COVID-19 typically have longer periods of ventilation than patients with other viral pneumonias [ 60 ], the use of tracheostomy to aid weaning from ventilatory support should be considered [ 61 ], which may ease the burden upon critical care resources [ 62 ]. Angel et al showed that early tracheostomy in COVID-19 patients can be performed with improved patient prognosis [ 63 ]. Reported rates of tracheostomies during the coronavirus pandemic were significantly higher than those of pre-pandemic [ 61 , 64 , 65 ].…”
Section: Main Textmentioning
confidence: 99%
“…None of the eight providers performing the tracheostomies had any symptoms of COVID-19 infection or tested positive for the virus following the procedures. A later propensity score matched analysis of 205 patients at our institution who underwent tracheostomy (195 via our novel PDT protocol) compared patients who underwent early tracheostomy (median = 9 days of MV), late tracheostomy (median = 19 days of MV), or no tracheostomy (14). Compared to patients who did not require tracheostomy, early PDT was associated with more days of MV but higher probability of being liberated from the ventilator and lower mortality.…”
Section: Tracheostomy and Bronchoscopy For Covid-19 Respiratory Failurementioning
confidence: 99%